Large cell neuroendocrine carcinoma of the lung presenting as pseudoachalasia: a case report - Anaizi, Ahmad (J Med Case Rep, 2015)
INTRODUCTION: Pseudoachalasia is a rare disease that accounts for only a small percentage of patients with dysphagia. Neuroendocrine tumors are rare malignancies that most commonly originate within the gastrointestinal tract, with the next most common site being the lungs. Esophageal neuroendocrine tumors are the least common site within the gastrointestinal tract. Pseudoachalasia can be secondary to a malignant process within the body. Its typical characteristic in elderly patients is a short duration of symptoms with substantial weight loss. CASE PRESENTATION: A 68-year-old woman presented with worsening dysphagia that had started six months after the resection of a large cell neuroendocrine carcinoma of the lung in 2011. An extensive work-up in 2012, including esophagogastroduodenoscopy, chest computed tomography and positron emission tomography, was unremarkable. Esophageal manometries revealed findings characteristic of achalasia. A repeat esophagogastroduodenoscopy in January of 2014 revealed a nearly circumferential ulcerated, fungating mass in her distal esophagus. Biopsy results confirming a recurrence of her large cell neuroendocrine carcinoma. CONCLUSION: We report a case of pseudoachalasia due to metastatic large cell neuroendocrine carcinoma of the lung. Our patient had an exceptionally prolonged duration of symptoms preceding the local esophageal recurrence, which was eventually revealed via endoscopy.